1998
DOI: 10.3171/jns.1998.89.1.0157
|View full text |Cite
|
Sign up to set email alerts
|

Posterior ventricular catheter burr-hole localizer

Abstract: Proper ventricular catheter placements are associated with improved shunt performance. When placing ventricular catheters via the posterior approach, the surgeon must determine an optimum trajectory and then pass a catheter along that trajectory. The incidence of optimal posterior catheter placements is increased by using a posterior catheter guide (PCG); however, errors may still occur because of poor selection of a posterior burr-hole site. In this report an easy-to-use posterior burr-hole localizer (Localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The third is to use generic stereotactic guides. The use of at least one stereotactic guide achieves rapid, accurate targeting from the occipital approach, 17,18 although the universal accuracy of generic guides has been challenged. 16 The advent of catheter introducers for use with patient-specific frameless stereotaxy provides an elegant solution that should be formally trialled for routine placement of occipital ventricular catheters.…”
Section: Discussionmentioning
confidence: 99%
“…The third is to use generic stereotactic guides. The use of at least one stereotactic guide achieves rapid, accurate targeting from the occipital approach, 17,18 although the universal accuracy of generic guides has been challenged. 16 The advent of catheter introducers for use with patient-specific frameless stereotaxy provides an elegant solution that should be formally trialled for routine placement of occipital ventricular catheters.…”
Section: Discussionmentioning
confidence: 99%
“…9,13) Investigation of a posterior ventricular catheter burr hole localizer employing the normally located superior orbital rim and superior attachment point of the ear as reference points showed that localization of the burr hole relative to the inion should not be applied because of the variations in this landmark. 9) The present retrospective analysis also showed that the described conventional standard occipital puncture might result in incorrect catheter emplacement and the ideal external aim points could not be standardized because of the wide varia- tion in the landmarks. We believe that the aim point should be decided based on preoperative individual radiological measurements, although this primitive process takes time.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other stereotactic aids designed to reduce variability of measurements and trajectories based on generic landmarks have been developed and shown to be of some value, although the uptake of these techniques by other surgeons is unknown. [10][11][12] Patient-specific frameless, frame-based or real-time ultrasound stereotaxy based on preoperative or intraoperative imaging is likely to improve accuracy at the expense of time taken in scanning and registration of fiducials but has not been systematically studied to determine the risk-benefit profile of this innovation.…”
Section: Introductionmentioning
confidence: 99%